Killer analytics top 20 metrics missing from your balance sheet - Brown, Mark Graham (Wiley, 2013)
"Killer Analytics shows businesses how analytics are being applied to measure components of business performance that traditionally are not measured. New areas include innovation, sustainability, risk, project management, and others. The book will show the value of measuring each area and then provide implementation tips."--
Includes index. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Organizational effectiveness -- Evaluation; Performance -- Management; Industrial efficiency -- Evaluation; Performance technology -- Management; Efficacité organisationnelle; Évaluation; Rendement au travail; Gestion; Efficience dans l'industrie; Évaluation; BUSINESS & ECONOMICS; Strategic Planning; Industrial efficiency; Evaluation; Organizational effectiveness; Evaluation; Performance; Management